Effect of Seed-borne Fungi on the Germinating Seeds and their Bio-control in Maize (Journal of Environmental Science and Natural Resources, 2012)
An experiment was conducted in Seed Pathology Center, Bangladesh Agricultural University, Mymensingh to determine the efficacy of biocontrol means (BAU-Biofungicide, Garlic extract and Neem extract) in controlling seedborne fungal diseases of maize (Zea mays). In laboratory experiment, the seeds of maize cultivars cv. Badsha-1, Khai Bhutta, Bornali, Mohor, BARI Bhutta- 5 and BARI Bhutta- 6 were tested by blotter method. The identified  fungi associated with the seeds were A. niger, A. flavus, Fusarium sp., P. oxalicum, C. lunata and R. stolonifer. The seed samples were treated with BAU-Biofungicide @ 2.5% of seed weight, neem extract@ 1:2 w/v and 1:3 w/v and garlic extract @ 1:2 w/v and 1:3 w/v to control the seed-borne pathogens. The effective results were recorded as regards to the highest germination (84.5%) reflected the lowest disease incidence (4.0%) recorded in BAUBiofungicide treated seeds followed by other treatment. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11564 J. Environ. Sci. & Natural Resources, 5(1): 117 - 120, 2012